Pengaruh Kerja Sama Usaha terhadap Produktivitas Kerja Anggota Kelompok Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS) - Panorama, Maya (Islamic Economics Program, Faculty of Islamic Economics and Business, 2017)
This research aims to explore and find the determinant factors as it is important for the development of group UPPKS management in Kecamatan Sukarami Palembang through a quntitative descriptive approach.The number of respondents was limited for 7 groups that are still active in Kecamatan Sukarami. The result showed that the cooperative effort influence to productivity. The findings of this study indicate that the lack of funds/start-up capital has not gained sufficient leverage; the absence of other sources of funding, in fact, almost all are individual business, so that managed such as savings and credit groups. Growing effort is being supported by additional capital that sought its own members, as well as the selection of profitable business activities. Group leader and members favored form of technical training, certain items are more salable. More individual businesses selling food and beverages are for their money-faster turnaround, rest handicraft products do not sell quickly, and thus this is the advantage of learning process through UPPKS.